2005
DOI: 10.1038/sj.mp.4001711
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in bipolar disorder: evidence from magnetic resonance spectroscopy research

Abstract: Magnetic resonance spectroscopy (MRS) affords a noninvasive window on in vivo brain chemistry and, as such, provides a unique opportunity to gain insight into the biochemical pathology of bipolar disorder. Studies utilizing proton ( 1 H) MRS have identified changes in cerebral concentrations of N-acetyl aspartate, glutamate/glutamine, choline-containing compounds, myo-inositol, and lactate in bipolar subjects compared to normal controls, while studies using phosphorus ( 31 P) MRS have examined additional alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
315
3
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(336 citation statements)
references
References 136 publications
(154 reference statements)
11
315
3
3
Order By: Relevance
“…Studies using proton ( 1 H) MRS have identified changes in cerebral concentrations of N-acetyl aspartate (NAA), glutamate/glutamine (Glx), cholinecontaining compounds, myo-inositol (mI), and lactate in bipolar subjects compared with normal controls. 148 Studies using phosphorus ( 31 P) MRS have examined additional alterations in levels of phosphocreatine (PCr), phosphomonoesters (PMEs), and intracellular pH (pHi). 149 These seemingly disparate findings of increased lactate and GLX, decreased NAA, and decreased pHi in bipolar subjects suggest a shift away from oxidative phosphorylation toward glycolysis, leading to reduced total energy output and efficiency (reviewed in Stork and Renshaw 2005).…”
Section: Stress and Glucocorticoids Modulate Neural Plasticity: Implimentioning
confidence: 99%
See 2 more Smart Citations
“…Studies using proton ( 1 H) MRS have identified changes in cerebral concentrations of N-acetyl aspartate (NAA), glutamate/glutamine (Glx), cholinecontaining compounds, myo-inositol (mI), and lactate in bipolar subjects compared with normal controls. 148 Studies using phosphorus ( 31 P) MRS have examined additional alterations in levels of phosphocreatine (PCr), phosphomonoesters (PMEs), and intracellular pH (pHi). 149 These seemingly disparate findings of increased lactate and GLX, decreased NAA, and decreased pHi in bipolar subjects suggest a shift away from oxidative phosphorylation toward glycolysis, leading to reduced total energy output and efficiency (reviewed in Stork and Renshaw 2005).…”
Section: Stress and Glucocorticoids Modulate Neural Plasticity: Implimentioning
confidence: 99%
“…148 Studies using phosphorus ( 31 P) MRS have examined additional alterations in levels of phosphocreatine (PCr), phosphomonoesters (PMEs), and intracellular pH (pHi). 149 These seemingly disparate findings of increased lactate and GLX, decreased NAA, and decreased pHi in bipolar subjects suggest a shift away from oxidative phosphorylation toward glycolysis, leading to reduced total energy output and efficiency (reviewed in Stork and Renshaw 2005). 148 Mitochondria play a critical role in maintaining calcium homeostasis.…”
Section: Stress and Glucocorticoids Modulate Neural Plasticity: Implimentioning
confidence: 99%
See 1 more Smart Citation
“…As reviewed elsewhere (Moore and Galloway, 2002;Stork and Renshaw, 2005;Stanley, 2002;Strakowski, 2005), resonances in the 1 HMR spectrum can be reliably quantified for several metabolites with brain concentrations in the millimolar range including N-acetyl-aspartate (NAA), a marker of neuronal viability; the excitatory amino-acid glutamate (Glu); glutamine (Gln), the glial cell reservoir storage form of glutamate; the sum of Glu and Gln (Glx); creatine + phosphocreatine (Cr), a measure of energy utilization which, given its relative stability, has historically been used as an 1 HMRS internal standard; choline related compounds (Cho) including glycerophosphocholine, phosphocholine, and acetylcholine some of which are involved in membrane metabolism; and myo-inositol (mI), a component of the cellular phosphoinositol-cycle second-messenger system.…”
Section: Introductionmentioning
confidence: 99%
“…fT1ρ mapping is of particular interest to study in bipolar disorder because the illness has been associated with metabolic abnormalities, in particular mitochondrial dysfunction (Clay, Sillivan, & Konradi, 2011; Kato, 2007; Stork & Renshaw, 2005). MR spectroscopy studies have shown that baseline pH is reduced (i.e., more acidic) in the anterior cingulate in people with bipolar disorder in the euthymic state compared to normal controls (Kato, Kunugi, Nanko, & Kato, 2000; Kato et al., 1998).…”
Section: Introductionmentioning
confidence: 99%